Alternatives of microclimate control in orchards - Lakatos, László; Szél, János; Nyéki, József; Szabó, Zoltán; Soltész, Miklós (Acta Agraria Debreceniensis, 2012)
The aim of the study was to find out which of the methods used to avoid damages of late frosts would be the most effective for the fruit growing practice. We tested the antifrost irrigation method in Debrecen-Pallag. For that purpose microjet sprayers are used, which are thrifty and does not need for that purpose large containers. With the aim to secure an even distribution of water, the sprayers are distributed on three levels: above and inside of the crown as well as on the level of trunks. On a large scale, a single microjet above the crown level would be sufficient. By means of a detailed analysis  served to set the optimum intervals between spraying phases: with each 15, 10, 5 and 3 minutes during half a minute. The synchronous presence of water and ice below the freezing point, the released freezing heat plus the water used much above the freezing point(9–10 °C) altogether maintains the temperature above around 0 °C near the flowers or growing fruitlets, meanwhile, the surrounding air cools down to -8 °C. The effectiveness of the generally used antifrost would be increased substantially by the former application of cooling irrigation, which delays the blooming date.